EFEKTIVITAS GAME-BASED LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS: SYSTEMATIC LITERATURE REVIEW - Nur Atika, Rassya; Mutaqin, Anwar; Nandang Mustafa, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low mathematical conceptual understanding at the secondary education level demands innovative learning strategies. This study aims to analyze the effectiveness of Game-Based Learning (GBL) on students' mathematical conceptual understanding through a systematic literature review. The method employed is a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. Data were collected from Google Scholar databases using the Publish or Perish application within the 2021 – early 2026 period. Out of 123 identified articles, 11 experimental articles met the inclusion criteria for in-depth analysis. The results indicate that the application of GBL, particularly through platforms such as Quizizz and Wordwall, exerts a significant positive influence (p < 0.05) on students' conceptual understanding. This improvement is evidenced by various measurement indicators in the reviewed literature, including N-Gain scores in the medium to high categories, as well as significant mean differences. Features like instant feedback and visualization capabilities in game-based media are proven to help students grasp abstract concepts more interactively. In conclusion, GBL has the potential to be an effective alternative learning strategy for strengthening students' mathematical conceptual mastery in secondary schools and is recommended as an alternative learning media in the classroom.